75%. Just divide 15/20 and you will get .75 then multiply by 100 to turn the decimal to a percent
Answer:
translate this to English and I'll help!(:
Answer:
64°
Step-by-step explanation:
In circle with center P, AD is diameter.
![\therefore m\angle DPE + m\angle APE = 180\degree \\\therefore (33k-9)\degree + 90\degree = 180\degree \\\therefore (33k-9)\degree = 180\degree -90\degree \\\therefore (33k-9)\degree = 90\degree \\\therefore 33k-9 = 90\\\therefore 33k= 90+9\\\therefore 33k= 99\\\therefore k= \frac{99}{33}\\\therefore k=3\\ m\angle CPD = (20k +4)\degree \\\therefore m\angle CPD = (20\times 3 +4)\degree \\\therefore m\angle CPD =(60+4)\degree \\\therefore m\angle CPD =64\degree \\m\overset {\frown}{CD} = m\angle CPD\\\therefore m\overset {\frown}{CD} = 64\degree](https://tex.z-dn.net/?f=%20%5Ctherefore%20m%5Cangle%20DPE%20%2B%20m%5Cangle%20APE%20%3D%20180%5Cdegree%20%5C%5C%3C%2Fp%3E%3Cp%3E%5Ctherefore%20%20%2833k-9%29%5Cdegree%20%2B%2090%5Cdegree%20%3D%20180%5Cdegree%20%5C%5C%3C%2Fp%3E%3Cp%3E%5Ctherefore%20%2833k-9%29%5Cdegree%20%20%3D%20180%5Cdegree%20-90%5Cdegree%20%5C%5C%3C%2Fp%3E%3Cp%3E%5Ctherefore%20%20%2833k-9%29%5Cdegree%20%20%3D%2090%5Cdegree%20%5C%5C%3C%2Fp%3E%3Cp%3E%5Ctherefore%20%2033k-9%20%3D%2090%5C%5C%3C%2Fp%3E%3Cp%3E%5Ctherefore%2033k%3D%2090%2B9%5C%5C%3C%2Fp%3E%3Cp%3E%5Ctherefore%20%2033k%3D%2099%5C%5C%3C%2Fp%3E%3Cp%3E%5Ctherefore%20%20k%3D%20%5Cfrac%7B99%7D%7B33%7D%5C%5C%3C%2Fp%3E%3Cp%3E%5Ctherefore%20%20k%3D3%5C%5C%3C%2Fp%3E%3Cp%3E%3C%2Fp%3E%3Cp%3E%20m%5Cangle%20CPD%20%3D%20%2820k%20%2B4%29%5Cdegree%20%5C%5C%3C%2Fp%3E%3Cp%3E%5Ctherefore%20m%5Cangle%20CPD%20%3D%20%2820%5Ctimes%203%20%2B4%29%5Cdegree%20%5C%5C%3C%2Fp%3E%3Cp%3E%5Ctherefore%20m%5Cangle%20CPD%20%3D%2860%2B4%29%5Cdegree%20%5C%5C%3C%2Fp%3E%3Cp%3E%5Ctherefore%20m%5Cangle%20CPD%20%3D64%5Cdegree%20%5C%5C%3C%2Fp%3E%3Cp%3E%3C%2Fp%3E%3Cp%3Em%5Coverset%20%7B%5Cfrown%7D%7BCD%7D%20%3D%20m%5Cangle%20CPD%5C%5C%3C%2Fp%3E%3Cp%3E%5Ctherefore%20m%5Coverset%20%7B%5Cfrown%7D%7BCD%7D%20%3D%2064%5Cdegree%20%20%3C%2Fp%3E%3Cp%3E)
Answer:
The answer is A.
Step-by-step explanation:
So we have the two equations:
![3x+y=1\\y+4=5x](https://tex.z-dn.net/?f=3x%2By%3D1%5C%5Cy%2B4%3D5x)
To make a substitution of the second equation into the first equation, we need to isolate the <em>y </em>variable in the second equation. Thus:
![y+4=5x\\y=5x-4](https://tex.z-dn.net/?f=y%2B4%3D5x%5C%5Cy%3D5x-4)
Now, we can substitute this into the first equation. Therefore:
![3x+y=1\\3x+(5x-4)=1\\3x+5x-4=1](https://tex.z-dn.net/?f=3x%2By%3D1%5C%5C3x%2B%285x-4%29%3D1%5C%5C3x%2B5x-4%3D1)
Answer:
42
Step-by-step explanation:
First condense all the numbers with exponents:
3² x 5³x 8 divided by 3 x 5³ x 8
27 x 125 x 8 divided by 3 x 27 x 8
Then multiply 27 , 125 ,and 8
27 x 125 x 8 =27000
Then multiply 3, 27 ,and 8
3 x 27 x 8 = 648
Then divide 27000 by 648
27000 / 648 = 41.6666666667
Which rounds to about: 42